The Read Feed. Issue 1 (3rd April 2022) - Johnson, Catherine; Parang, Elizabeth; Rosenblatt, Stephanie
Abstract: Elizabeth Parang reviews Transfer Student Success: Academic Library Outreach and Engagement ; Stephanie Rosenblatt reviews The One-Shot Library Instruction Survival Guide, Third Edition.